Comparison of uterine transcornual diameter using 3D-transvaginal ultrasound between adenomyotic and normal uteri - El-Habashy, Ahmed; Farag, Mohamed; El-Said, Rehab (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Various sonographic markers for diagnosis of adenomyosis had been published by the morphological uterus sonographic assessment (MUSA) group. Most of their data based on two dimensional transvaginal ultrasound (2D-TVUS) findings. Our study aimed to find if there is a relation between the presence of adenomyosis uteri and the transcornual diameter. Methods: We had studied 768 cases (33-44 years old) who were referred to Habashy 4D scan center (Alexandria; Egypt) between August 2019 and August 2023. We had divided cases into two groups; each with 384 cases. First group has diffused adenomyosis and the second group has normal uterus. We had diagnosed adenomyosis based in the presence of ≥4 of the MUSA criteria. In the control group; we had selected cases with normal sized uterus. We had compared the transcornual diameter of the uterine cavity in the coronal plane between both groups using 3D-TVUS during the luteal phase of the cycle. Results: The mean transcornual diameter in cases who had adenomyosis was 39 mm (±6 mm). The mean transcornual diameter in the control group was 24 mm (±8 mm). Conclusions: The mean transcornual diameter of the uterine cavity in the coronal plane using luteal 3D-TVUS in adenomyotic uteri was statistically significantly higher than in the controls. To the best of our knowledge, our study is the first study in literature that compare the transcornual diameter adenomyotic and normal uteri. We can extrapolate from our data to assume that transcornual diameter <35 mm can be used as an exclusion for diagnosis of cases as having adenomyosis uteri.